Government Regulations for Standardizing Riders Way of Working and also Providing more Earning Opportunities for Them - Muhammad Younus; Achmad Nurmandi; Rashid Minhas; Abdul Rehman; Hajira Gul; Ibrahim Shah; Rendra Agusta (International Journal of Business and Applied Economics, 2023)
The researchers wrote this article to make the government realize the criticality of the problems in the logistics sector's way of handling riders and to give a clear understanding of the issue. The goal is to standardize riders' ways of working through government regulations and guidelines. Thus, we will begin with the challenges currently facing riders in detail and context and then provide ways to standardize the procedure and reduce the issue. Finally, we will discuss ways to give riders more ways to earn so they can increase their basic salary without being overworked and create new business models that can boost the economy by providing unique employment opportunities.